Impact of the Health-Smart Holistic Health Program: A CBPR Approach to Improve Health and Prevent Adverse Outcomes for Black Older Adults. Issue 4 (November 2022) - Tucker, Carolyn M.; Wippold, Guillermo M.; Roncoroni, Julia; Henry, Meagan A.; Klein, Kirsten G.; Garrepy, Matthew; Ateyah, Wafaa; Burwell, Alexanderia; Walker, Hermonyone; Clements, Leslie M.; Kelly Pryor, Brandy N.; Fullwood, Dottington
Black older adults experience poorer health and health-related outcomes than their non-Hispanic White counterparts. Novel, tailored strategies to promote health and prevent adverse health-related outcomes that are aligned with the preferences and values of Black older adults are needed given the limited effectiveness of "one-size-fits-all" approaches. The present study evaluated the impact of a 9-week, community-based participatory research-informed program called the Health-Smart Holistic Health Program for Seniors that aimed to improve health and prevent adverse outcomes among Black older adults by targeting body mass index (BMI), loneliness, food insecurity, and physical and psychological health-related quality of life. Participants ( N = 139) were community dwelling, economically disadvantaged Black older adults living in an underserved area. Results indicated that from pre-intervention to post-intervention there were (a) significant decreases in BMI, loneliness, and food insecurity and (b) significant increases in the participating seniors' psychological and physical health-related quality of life. Most of these changes were maintained at a 3-month post-intervention follow-up. These results have implications for similar efforts attempting to prevent adverse health outcomes among Black older adults, a high-risk and understudied group. Such efforts should be tailored and should address factors at multiple levels.